Career choices at a public higher education institution (IPTA): An examination of the social cognitive model of career self-management - Meng, Foo Guan; Wan Jaafar, Wan Marzuki (Human Resources Management Academic Research Society (HRMARS), 2024)
This study aimed to examine the impact of social support and personality traits (conscientiousness and neuroticism) on self-efficacy in career decision-making, outcome expectations, and the certainty of career choice among students in one public higher education institution (IPTA) located in Selangor. This quantitative study utilised survey research as the main method for data collection. A questionnaire which consisted six parts: Part A related to students’ demographic; Part B, Career Decision Self-Efficacy Scale-Short Form (CDSE-SF); Part C, Career Outcome Expectations Scale; Part D, Multidimensional Scale of Perceived Social Support; Part E, Career Exploratory Plans or Intentions Questionnaire (CEPI); and Part F, NEO-FFI (NEO Five-Factor Inventory); was employed and distributed virtually to 377 IPTA students whom sampled through voluntary sampling. Based on the study’s findings, personality traits, particularly conscientiousness, have significant impact and significant positive relationships with self-efficacy (r=0.233, p=0.000), outcome expectations (r=o.268; p=0.000), and career explorations goals (r=0.916, p=0.000; at p<0.05) - the important aspects of Career Self-Management (CSM) model. Contrarily, there was the absence of significance between social support with the previously mentioned vital aspects of CSM model. This study implied that students’ beliefs and positive outcome expectations are the most important and significant predictors for their career exploration goals.